A novel simplified precooled airbreathing engine cycle: Thermodynamic performance and control law. (15th April 2022) - Zou, Zhengping; Wang, Yifan; Du, Pengcheng; Yao, Lichao; Yang, Shunhua; Zhang, Wanzhou; Luo, Jiamao
Highlights: A novel thermodynamic cycle of precooled airbreathing engine HAPE is proposed. A better compromise between the specific impulse and system complexity is achieved. The charge control of HAPE has a wider range of thrust regulation. The bypass control of HAPE is easier to implement but the regulation range is limited. Abstract: The precooled airbreathing engine is a promising propulsion concept for horizontal takeoff and landing hypersonic aircraft. The helium closed cycle has been introduced in the precooled airbreathing engine such as the Synergetic Air-Breathing Rocket Engine to enhance safety and thermal efficiency of the engine, whereas increasing the system complexity inevitably. To achieve a better compromise between the specific impulse and system complexity, a novel thermodynamic cycle layout was proposed in this paper. The air was moderately precooled in the precooler at high flight Mach number, and a relatively simple two branches splitting-cooling-recompression scheme was adopted in the helium closed cycle, as well as a bypass engine path with small bypass ratio was introduced to burn the excess hydrogen. Firstly, the parametric analysis of key design variables and performance optimization were carried out at the Mach 5.0 design point, and the specific impulse could reach a value of up to 3282 s. The engine was controlled by adjusting the air & fuel path and the helium closed cycle simultaneously. As for the air & fuel path, the amount of liquid hydrogen used for cooling and combustion could be equilibrium by adjusting the equivalence ratio in the bypass combustor and the area of bypass nozzle throat concurrently. In the helium closed cycle, the charge control and bypass control methods were adopted separately. The engine thrust could be effectively regulated over a wider range as well as all the main components work stably under the charge control. The results show that the bypass control is easier to implement but the regulation range of thrust is limited. The overall engine performance calculated along a typical flight trajectory shows that this simplified precooled airbreathing engine cycle has comparatively high specific impulse from take-off to Mach 5.0. As the helium closed cycle layout is relatively simple, it is maybe easier to achieve engineering realization.